2000
DOI: 10.1111/j.1651-2227.2000.tb02778.x
|View full text |Cite
|
Sign up to set email alerts
|

Parents' perception of mental development and behavioural problems in 8 to 9‐year‐old children

Abstract: Larsson J-O, Lichtenstein P, Fried I, El-Sayed E, Rydelius PA. Parents' perception of mental development and behavioural problems in 8 to 9-year-old children. Acta Paediatr 2000; 89: 1469-73. Stockholm. ISSN 0803-5253A slow maturational rate may be an underlying antecedent of a psychiatric disorder. If this is correct, differences in behavioural problems could be related to the maturity level in children of the same chronological age. The aim of the study was to compare the parents' perceptions and assessments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…It should be noted that conflicting results are reported in the literature (e.g., Levy, Hay, McLaughlin, Wood & Waldman, 1996). Nevertheless, two previous reports (Larsson, Lichtenstein, Fried, El-Sayed & Rydelius, 2000;Eley, Lichtenstein & Moffitt, 2003) have shown that mean levels in emotional and behavior problems according to CBCL (Achenbach, 1991) in the current TCHAD sample is similar to what has been found in other Swedish samples. Further, the prevalence of children having eight or more ADHD symptoms in the current sample was 4.7% at age 8-9 and 3.1% at age 13-14 (Paper I), numbers that are in line with other reports from Sweden (Kardesjö & Gillberg, 1998).…”
Section: Generalizabilitysupporting
confidence: 43%
“…It should be noted that conflicting results are reported in the literature (e.g., Levy, Hay, McLaughlin, Wood & Waldman, 1996). Nevertheless, two previous reports (Larsson, Lichtenstein, Fried, El-Sayed & Rydelius, 2000;Eley, Lichtenstein & Moffitt, 2003) have shown that mean levels in emotional and behavior problems according to CBCL (Achenbach, 1991) in the current TCHAD sample is similar to what has been found in other Swedish samples. Further, the prevalence of children having eight or more ADHD symptoms in the current sample was 4.7% at age 8-9 and 3.1% at age 13-14 (Paper I), numbers that are in line with other reports from Sweden (Kardesjö & Gillberg, 1998).…”
Section: Generalizabilitysupporting
confidence: 43%